How do sparkling wine producers adopt a sub-appellation? Evidence from an exploratory study on heroic Prosecco Superiore Rive - Luigino Barisan; Luigi Galletto (Wine Economics and Policy, 2021)
This exploratory paper investigates why sparkling wine houses producing Conegliano Valdobbiadene Prosecco Protected Designation of Origin (CVPP) wines decided to adopt the sub-appellation "Rive" to increase the value of their wines. We estimated both logistic and generalized linear models to explain Rive sub-appellation (SA) firms' choice and market share, respectively. By using data gathered from CVPP producers, we divided wineries into two groups, namely, those that adopted the Rive SA and those that did not. By means of a stepwise procedure, we categorized factors that were likely to explain the Rive SA choice within a set of structural, marketing and wine tourism-related variables. The results showed that structural drivers such as the human capital of younger producers, firm size, resource endowments, wine production, and involvement in ad hoc promotional activities (i.e., Primavera del Prosecco) have the greatest effects on the choice of Rive SA. On the other hand, the effects of small sizes, cellar door sales, and key CVPP wine tourism events have emerged as vital factors in the growth of Rive SA in terms of market share. The adoption of the Rive SA may play an important role in supporting and valuing the work of a vine-growers community who have been able to transform the difficulties and the passion of vine cultivation on steep slopes parcels into distinguishing features and may help the CVPP Tutelary Consortium appropriately undertake promotional policies to differentiate wines and improve competitiveness. This could have positive effects on wine tourism, hospitality, and winery visits considering the recent recognition of the CVPP as the 55th Italian UNESCO World Heritage site.
Keywords: 330; sub-geographical indication; Prosecco sparkling wine firms; intraregional wine differentiation; steep-slope viticulture; market differentiation; wine tourism strategies